EFFICIENCY INDICES OF INVESTMENT IN IT PROJECTS WITH UNEQUAL LIVES - Nastas, Vasile; Bolun, Ion; Ghetmancenco, Svetlana (SWorldJournal, 2022)
Theoretical results not always give an unambiguous answer regarding the preference of using the indices of IT project investment efficiency. To complement some of such results, the Net Present Value (NPV), Profitability (PI), Equivalent Annual NPV (EANPV)